Lived experiences of parents on school-aged children with developmental delay : a proposed home intervention program - Bautista, Allysandra G. (Bulacan : National University, 2024)
This study revealed the different manifestations of developmental delays school-aged children.
Chapter I. The Problem and its background -- Chapter II. Literature Review -- Chapter III. Methodology of the study -- Chapter IV. Presentation, Analysis and Interpretation of Data -- Chapter V. Summary, Conclusion and Recommendation -- References.
Qualitative Research
Includes bibliographical references.
Keywords: SCHOOL-AGED CHILDREN; DEVELOPMENTAL DELAYS